Multivariate Risk Independence and Functional Forms for Preferences and Technologies - Epstein, Larry G. (Econometrica, 1980)
The comparative static effects of increased uncertainty in standard two-period models of consumer and producer behavior under uncertainty have been shown in [10 and 11] to be complex. Two principal objectives of this paper are: (i) to describe some assumptions, forms of risk independence, about preferences and technologies, that simplify the behavioral effects of increased variability; and (ii) to characterize the preferences and technologies that are consistent with risk independence. The theory of duality plays an important part in the analysis.